Strategi Partisipatif untuk Meningkatkan Keterlibatan Siswa pada Pembelajaran Biologi: (Participatory Strategies to Increase Student Involvement in Biology Learning) - Maria Kezia Gaghunting; Jessica Elfani Bermuli (BIODIK, 2023)
Student involvement is essential to do in learning because it can affect student achievement. Student involvement can determine they to get meaningful learning. However, in reality, there is still a lack of student involvement in learning. This was observed from the lack of student involvement in expressing opinions during the learning process. Educators need to increase student involvement as subjects in learning. The application of participatory strategies can be a solution to increase student involvement in learning. The purpose of writing this journal is to find out the role of participatory strategies to increase student involvement in Biology learning. The method used is a literature review and qualitative descriptive. Each student is an image and likeness of God who has various characters. Although they have various characters that affect students in learning, they are all valuable in the eyes of the Lord God. In understanding students' abilities, Christian anthropology studies are needed which study character, goodness, and the human person. The application of participatory strategies can increase the involvement of students in learning. The results of the application of the participatory strategy showed that the students were able to achieve the three observed indicators of involvement. The participatory strategy is implemented according to the implementation steps through two methods, namely, discussion and think, pair, and share. Abstrak. Keterlibatan siswa merupakan hal yang esensial untuk dilakukan pada pembelajaran karena mampu memengaruhi prestasi belajar siswa. Keterlibatan siswa juga dapat menentukan dalam memperoleh pembelajaran yang bermakna. Namun pada kenyataannya, masih terdapat kurangnya keterlibatan siswa dalam pembelajaran. Hal tersebut teramati dari kurangnya keterlibatan siswa dalam menyampaikan pendapat selama pembelajaran berlangsung. Pendidik perlu meningkatkan keterlibatan siswa sebagai subjek belajar dalam pembelajaran. Penerapan strategi partisipatif dapat menjadi solusi untuk meningkatkan partisipasi siswa dalam pembelajaran. Tujuan penulisan jurnal ini adalah untuk mengetahui peranan strategi partisipatif dalam meningkatkan keterlibatan siswa pada pembelajaran Biologi. Metode yang digunakan adalah kualitatif deskriptif yang dilengkapi dengan kajian literatur. Setiap siswa merupakan gambar dan rupa Allah yang memiliki beragam karakter. Karakter yang beragam sehingga memengaruhi siswa dalam pembelajaran, mereka semua berharga di mata Allah. Dalam memahami karakter siswa, diperlukan studi antropologi yang mempelajari tentang karakter, kebaikan, dan pribadi manusia. Penerapan strategi partisipatif dapat meningkatkan keterlibatan siswa dalam pembelajaran Biologi. Hasil penerapan strategi partisipatif menunjukkan bahwa para siswa dapat mencapai ketiga indikator keterlibatan yang diamati. Strategi partisipatif diimplementasikan sesuai dengan langkah-langkah penerapannya dengan menggunakan dua metode yaitu, metode diskusi dan think, pair, and share.